`g(x) = (x^2 + 3)(x^2 - 4x)` Use the Product Rule to find the derivative of the function.

Textbook Question

Chapter 2, 2.3 - Problem 1 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

hkj1385's profile pic

hkj1385 | (Level 1) Assistant Educator

Posted on

`g(x) = (x^2 + 3)*(x^2 - 4x)`

`g'(x) = 2x(x^2 - 4x) + (2x-4)(x^2 + 3)`

`or, g'(x) = 2(x^3) - 8(x^2) + 2(x^3) + 6x - 4(x^2) - 12`

`or, g'(x) = 4x^3 - 12x^2 + 6x - 12`

`or, g'(x) = 2[2x^3 - 6x^2 + 3x - 6]`

` `

We’ve answered 318,915 questions. We can answer yours, too.

Ask a question